Research of Cycloidal Pump for Hybrid Transmission（E-CVT） - Shi Chongshi; Yan Chenxi; Huang Mingyu; Ni Hongjun (Jixie chuandong)
The oil pump equipped with E-CVT has the function of providing cooling lubrication flow and brake flow.In order to study the use characteristics of cycloidal pump as the power source of E-CVT hydraulic system，the mathematical model is established based on theoretical analysis，and the multi-domain simulation model including signal domain，hydraulic domain and mechanical domain is built by AMESim platform.The model is verified by experimental data.Based on the simulation model，the effects of oil temperature，rotation speed and load pressure on volumetric efficiency and flow characteristics are dynamically studied.At the same time，the low oil temperature start failure of the oil pump in the E-CVT is predicted by the model connection filter，oil sump and pipeline，which provides a reference for the subsequent fuel pump motor related strategy design.